Study the Art Forms of Installation Art by Female Artists in Thailand - Ophascharas Nandawan (Asian Creative Architecture, Art and Design : ACAAD, 2025)
This study focuses on analyzing the complex artistic expressions of Thai female artists, exploring the profound and multidimensional forms of artistic representation that present the unique perspectives and experiences of women in the art world. The article examines the key characteristics of complex artworks by Thai female artists, covering various aspects such as the integration of diverse techniques and media, the presentation of ideas that challenge social and gender norms, the use of new media technology in creative processes, and the interdisciplinary approach to art-making. Furthermore, it analyzes the methods Thai female artists employ to engage audiences, create complex narratives, and present diverse viewpoints through their works. This study aims to foster an understanding of the role and influence of Thai female artists in the development of complex artistic expressions, as well as the challenges and changes they bring to the contemporary art scene. This abstract provides an overview of the study that specifically focuses on the complex artistic expressions of female artists, identifying key issues and research objectives. It helps readers clearly understand the scope and significance of this topic.
Keywords: Cultural Industries and Urban Development